Developmental origins of chronic physical aggression a bio-psycho-social model for the next generation of preventive interventions. [article]. - Tremblay, Richard E.
This review describes a bio-psycho-social approach to understanding and preventing the development of chronic physical aggression. The debate on the developmental origins of aggression has historically opposed genetic and environmental mechanisms. Recent studies have shown that the frequency of physical aggression peaks in early childhood and then decreases until old age. Molecular genetic studies and twin studies have confirmed important genetic influences. However, recent epigenetic studies have highlighted the important role of environments in gene expression and brain development. These studies suggest that interrelated bio-psycho-social channels involved in the development of chronic physical aggression are generally the product of an intergenerational transmission process occurring through assortative mating, genetic inheritance, and the inheritance of physical and social environmental conditions that handicap brain functioning and support the use of physical aggression to solve problems. Given these intergenerational mechanisms and physical aggression onset in infancy, it appears clear that preventive interventions should start early in pregnancy, at the latest. -- (from the author)